Modified MOF synergistic resin-based composite material as well as preparation method and application thereof
The modified MOF synthesizing resin-based composite material UiO-66-NH2-SH@CR11 was solved by the one-pot method, which solved the problem of agglomeration and recycling of MOF materials in actual applications, and significantly improved the adsorption efficiency of heavy metals such as copper and antimony. , achieving efficient removal of heavy metals in polluted water bodies.
Patent Information
- Application Number
- CN202411574744.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art cannot provide MOF-resin composite materials with high efficiency adsorption of heavy metal ions (such as copper ions, antimony ions) and their preparation methods, and MOF materials have problems of agglomeration, recycling and difficult to predict performance in practical applications.
The modified MOF synthesizing resin-based composite material UiO-66-NH2-SH@CR11 was synthesized by one pot method, and the materials such as ZrCl4 and 2-aminoterephthalic acid were formed in the solvothermal reaction, thereby increasing the material's The specific surface area and active sites significantly improve the adsorption efficiency of heavy metal ions.
It significantly improves the adsorption effect of heavy metals such as copper and antimony, has strong anti-interference ability, and is suitable for the removal of toxic and harmful heavy metals in polluted water bodies.
Smart Images

Figure CN119192741A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pollutant treatment, and relates to a modified MOF synergistic resin-based composite material and a preparation method and application thereof. Background Art
[0002] An important way to realize the resource utilization of industrial wastewater is zero discharge of wastewater. A large amount of waste salt will be formed in the process of zero discharge of wastewater. Using waste salt as raw material in the chlor-alkali industry is an effective consumption channel. However, waste salt often contains a large amount of transition metal cations, which has an adverse effect on the ion membrane electrolysis process in the chlor-alkali process. Therefore, transition metal impurities must be removed before the chlor-alkali process so that the waste brine can meet the requirements of refined brine in the ion membrane electrolyzer. Resin adsorption is a commonly used secondary brine refining process. The heavy metals in the sample solution are adsorbed by a porous solid adsorbent to achieve the purpose of separating heavy metals. CR11 is a millimeter-sized transparent light yellow spherical particle containing rich iminodiacetic acid functional groups. It is an effective heavy metal adsorption resin, but its adsorption efficiency for trace heavy metals is limited.
[0003] MOF is a porous polymer compound composed of metal clusters and organic ligands, which has the advantages of large specific surface area, designable structure and function. The disadvantage of MOF material is that it is in powder form, which is not easy to recycle and reuse in practical applications. Loading functionalized MOF on the stationary phase bulk material can effectively prevent MOF agglomeration and improve its recovery rate. The specific surface area of the composite material is increased, which promotes the effective contact between pollutants and the active sites of the material, thereby increasing the adsorption efficiency and enhancing the adsorption selectivity. However, when loading MOF materials using the usual method, the resulting composite material may have low loading stability and MOF desorption. In addition, the mutual influence between the active sites of MOF and the bulk material also makes it difficult to speculate and predict the performance of the composite material, which greatly limits the application of MOF materials.
[0004] There are two methods for synthesizing MOF-based composite materials: one-pot method and step-by-step method. In the step-by-step method, metal ions or organic ligands are first combined with a stationary phase under certain reaction conditions, and then the organic ligands or metal ions are coordinated with the metal ions or organic ligands on the resin to form MOF. In the one-pot method, metal ions, organic ligands, stationary phases and other required raw materials are mixed together, and MOF is grown in situ on the stationary phase by a solvent thermal method. This method has simple process steps and is conducive to industrial production. However, since the mixture system in the one-pot method is often more complex, it is often necessary to optimize its process conditions in order to synthesize the expected material, thereby achieving the purpose of synthesizing MOF-based composite materials with good performance.
[0005] In the article "Photoinduction of Cu Single Atoms Decorated on UiO-66-NH2 for Enhanced Photocatalytic Reduction of CO2 to Liquid Fuels" (JACS, 2020, 142(45), 19339-19345), Li Yadong's research group pointed out that the ligand amino group of UiO-66-NH2 material has a certain adsorption and positioning effect on copper ions. Under the catalytic reduction reaction of visible light, the positioned copper ions can be reduced to single-atom copper catalysts, thereby achieving an improvement in the catalytic effect of carbon dioxide reduction.
[0006] Qi Youxiao et al. disclosed a new type of hollow UiO-66-NH2 material in the article "Preparation of Hollow UiO-66-NH2 Materials and Their Application in Electrochemical Simultaneous Detection of Lead and Copper Ions" (Journal of Qingdao University of Science and Technology, August 2020, Vol. 41, No. 4, pp. 27-35). A UiO-66-NH2 nanoparticle material with a fluffy outer layer was obtained by acetic acid etching after secondary growth. By utilizing the limiting capture effect of UiO-66-NH2 in this material on metal ions such as copper and lead, the material is modified in the detection electrode, which can achieve the effect of efficient and high-precision detection of metal ions in the solution.
[0007] Chinese invention patent CN105175295A provides a preparation of a thiol-functionalized MOFs material and its application in the adsorption and removal of heavy metal ions in water. The thiol-functionalized MOFs (UiO-66-SH) material can effectively adsorb and remove heavy metal ions such as copper, cadmium, lead, and mercury in water. The method steps are as follows: (1) first synthesizing a terephthalic acid organic ligand modified with a thiol group; (2) preparing and synthesizing a thiol-functionalized MOFs material UiO-66-SH by a solvent thermal method; (3) using the thiol-functionalized MOFs material UiO-66-SH as an adsorbent to adsorb and remove heavy metal ions such as copper, cadmium, lead, and mercury in water. This technology can efficiently adsorb and remove heavy metal ions such as copper, cadmium, lead, and mercury in water, and greatly improves its adsorption performance compared to ordinary UiO-66. In addition, the material can selectively adsorb and remove mercury ions under high concentration conditions, broadening the new application of MOFs materials.
[0008] Chinese invention patent CN106902649A provides a sulfur-modified MOF membrane with high clearance of heavy metal ions in blood and its preparation method. The method first prepares a thiol-modified MOF material or a bromine-substituted thiol-modified MOF material, then protects the thiol in the thiol-modified MOF material or the bromine-substituted MOF material to obtain a thiol-protected MOF, then reacts the thiol-protected MOF with a Grignard reagent to obtain a double-chained MOF material, and finally grafts the double-bonded MOF material on the surface of a polymer substrate material by pre-irradiation or co-irradiation to obtain a sulfur-modified MOF membrane. The MOF membrane provided by this technology has a high clearance of Cu in blood. 2+ 、Cd 2+ , Hg 2+ , Pb 2+ 、As 3+ Plasma has high cleaning performance and in-situ capture characteristics.
[0009] Chinese invention patent CN118745255A provides a thiol-modified MOF material, synthesis method and application. The material comprises a thiol-containing group modified on the surface of the zirconium cluster in UiO-66 by a Schiff base structure. This technology utilizes the strong complexation of thiol groups on lead ions, grafts abundant thiol active sites on the surface of MOF, and exhibits good adsorption capacity for lead ions, and has low modification cost, strong selectivity and good adsorption effect.
[0010] However, the prior art cannot provide a MOF-resin composite material having the ability to efficiently adsorb heavy metal ions (such as copper ions and antimony ions) and a preparation method thereof. Summary of the invention
[0011] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a modified MOF-enhanced resin-based composite material and a preparation method and application thereof.
[0012] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a modified MOF-enhanced resin-based composite material, comprising the following steps:
[0013] S1, mixing MOF raw materials, modifiers, resins and solvents, and stirring to obtain a mixture;
[0014] S2, subjecting the mixture obtained in step S1 to a solvothermal reaction to obtain a modified MOF-enhanced resin-based composite material;
[0015] Wherein, in step S1, the MOF raw material is composed of ZrCl4 and 2-aminoterephthalic acid, and the modifier is a carboxylic acid containing sulfur element; in step S2, the temperature of the solvent thermal reaction is 100-150°C.
[0016] Preferably, in step S1, the modifier is selected from at least one of thioglycolic acid, lipoic acid, and L-cysteine, more preferably thioglycolic acid.
[0017] Preferably, in step S1, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N,N-diethylformamide, more preferably N,N-dimethylformamide.
[0018] Preferably, in step S1, the resin is at least one of CR11 resin, D201 resin and D113 resin, more preferably CR11 resin.
[0019] Preferably, in step S1, the molar ratio of ZrCl4 to 2-aminoterephthalic acid is 0.95-1.05:1, more preferably 1:1.
[0020] Preferably, in step S1, the ratio of the mass of the MOF raw material, the mass of the modifier, the mass of the resin and the volume of the solvent is 0.5:0.1-7:0.5-5:10-30, in units of g:g:g:mL.
[0021] More preferably, in step S1, the ratio of the mass of the MOF raw material, the mass of the modifier, the mass of the resin and the volume of the solvent is 0.5:2:2.5:15, in units of g:g:g:mL.
[0022] Preferably, in step S2, the solvent thermal reaction time is 18-36 hours.
[0023] More preferably, in step S2, the temperature of the solvothermal reaction is 120° C., and the time of the solvothermal reaction is 24 h.
[0024] On the other hand, the present invention provides a modified MOF-enhanced resin-based composite material prepared by the above preparation method.
[0025] In another aspect, the present invention provides the use of the modified MOF-enhanced resin-based composite material prepared by the above preparation method in pollutant treatment.
[0026] Preferably, the pollutant is sewage.
[0027] More preferably, the pollutant is sewage containing copper ions and / or antimony ions.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention provides a one-pot method for synthesizing a modified MOF enhanced resin-based composite material UiO-66-NH2-SH@CR11. The method can effectively increase the specific surface area of the material, increase the number of active sites, significantly improve the effect of removing two heavy metals, copper and antimony, and has strong anti-interference ability. The modified MOF enhanced resin-based composite material can be used to remove toxic and harmful heavy metals in polluted water. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a scanning electron microscope (SEM)-energy dispersive spectroscopy (EDS) characterization result diagram of the modified MOF enhanced resin-based composite material prepared in Example 1; wherein (a), (b) and (c) respectively represent SEM photos of the modified MOF enhanced resin-based composite material at different magnifications, and the magnification of (a) is 100 times, the magnification of (b) is 1000 times, and the magnification of (c) is 10000 times; (d) represents the SEM photo of the internal cross-section of the modified MOF enhanced resin-based composite material, and the magnification of (d) is 100 times; (e) represents the EDS element quantitative spectrum of the rectangular selected area in (d).
[0031] Figure 2 It is the XRD diagram of the modified MOF enhanced resin-based composite material synthesized in Example 1, the MOF material synthesized in Comparative Example 2, and the CR11 resin.
[0032] Figure 3 This is a graph showing the nitrogen adsorption and desorption experimental results of the modified MOF-enhanced resin-based composite material synthesized in Example 1.
[0033] Figure 4 It is a bar graph of the equilibrium adsorption capacity of copper ions and antimony ions by the modified MOF enhanced resin-based composite material synthesized in Example 1, the MOF material synthesized in Comparative Example 2, and the CR11 resin. DETAILED DESCRIPTION
[0034] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0035] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0036] In the following examples, the sources of raw materials are as follows:
[0037]
[0038]
[0039] Example 1
[0040] The preparation method of the modified MOF enhanced resin-based composite material comprises the following steps.
[0041] (1) Place 0.2815 g of ZrCl4 and 0.2185 g of 2-aminoterephthalic acid in a beaker (the total mass of ZrCl4 and 2-aminoterephthalic acid is 0.5 g, and the molar ratio is 1:1). Add 2.5 g of CR11 resin, 1.5 mL (2.0 g) of thioglycolic acid and 15 mL of N,N-dimethylformamide to the beaker and stir for 6 h;
[0042] (2) pouring the mixture into a high-pressure reactor, placing the high-pressure reactor in a homogeneous reactor, and heating to 120°C at a heating rate of 5°C / min; reacting for 24 hours, and cooling to room temperature; centrifuging the obtained post-reaction mixed solution to separate the solid, washing it once with N,N-dimethylformamide and acetone, and then washing it three times with water, and then separating the solid, and freeze-drying it to obtain the MOF enhanced resin-based composite material UiO-66-NH2-SH@CR11.
[0043] Example 2
[0044] Compared with Example 1, the difference is that 1.5 mL of thioglycolic acid is replaced by 2.0 g of L-cysteine, and the rest is the same.
[0045] Example 3
[0046] Compared with Example 1, the difference is that 1.5 mL of thioglycolic acid is replaced by 2.0 g of lipoic acid, and the rest is the same.
[0047] Example 4
[0048] Compared with Example 1, the difference is that the amount of CR11 resin is changed to 5g, and the rest is the same.
[0049] Example 5
[0050] Compared with Example 1, the difference is that the amount of CR11 resin is changed to 0.5 g, and the rest is the same.
[0051] Example 6
[0052] Compared with Example 1, the difference is that the amount of thioglycolic acid is changed to 0.1g, and the rest is the same.
[0053] Example 7
[0054] Compared with Example 1, the difference is that the amount of thioglycolic acid is changed to 7g, and the rest is the same.
[0055] Example 8
[0056] Compared with Example 1, the difference is that the stirring time is changed to 12 hours, and the rest are the same.
[0057] Example 9
[0058] Compared with Example 1, the difference is that the solvent thermal reaction temperature is changed to 100° C., the solvent thermal reaction time is changed to 36 h, and the rest are the same.
[0059] Example 10
[0060] Compared with Example 1, the difference is that the solvent thermal reaction temperature is changed to 150° C., the solvent thermal reaction time is changed to 18 h, and the rest are the same.
[0061] Embodiment 11
[0062] Compared with Example 1, the difference is that the reaction time of the high-pressure reactor is changed to 18 hours, and the rest is the same.
[0063] Comparative Example 1
[0064] Compared with Example 1, the difference is that the temperature rising condition of the high pressure reactor is changed to be heated to 80° C. at a heating rate of 5° C. / min, and the rest are the same.
[0065] Comparative Example 2
[0066] Synthesis of a MOF material.
[0067] Place 0.2815 g of ZrCl4 and 0.2185 g of 2-aminoterephthalic acid in a beaker (the total mass of ZrCl4 and 2-aminoterephthalic acid is 0.5 g, and the molar ratio is 1:1). Add 1.5 mL (2.0 g) of thioglycolic acid and 15 mL of N,N-dimethylformamide to the beaker and stir for 6 h.
[0068] (2) The mixture was poured into a high-pressure reactor, which was placed in a homogeneous reactor and heated to 120° C. at a heating rate of 5° C. / min; the mixture was reacted for 24 h and then cooled to room temperature.
[0069] (3) The obtained mixed solution after the reaction was centrifuged to separate the solid, which was washed once with N,N-dimethylformamide and acetone, respectively, and then washed three times with water. The solid was then separated and freeze-dried to obtain the MOF enhanced resin-based composite material UiO-66-NH2-SH.
[0070] Effect evaluation
[0071] 1. Structural characterization of the modified MOF enhanced resin-based composite material prepared in Example 1
[0072] 1.1 Scanning electron microscopy (SEM)-energy dispersive spectroscopy (EDS) characterization
[0073] The JEOL JSM-IT500HR scanning electron microscope-energy dispersive spectrometer produced by JEOL Ltd. was used to analyze the material morphology and surface element composition. Figure 1 As shown. Figure 1 (a) Figure 1 (b) and Figure 1 (c) in the figure shows the morphology of the composite material at different magnifications, and it can be seen that MOF material is generated on the surface of the resin ball. Figure 1 (d) and Figure 1 (e) in the figure are the internal cross-section and elemental composition of the composite material. The results show that the zirconium element is only present in the MOF but not in the resin. Therefore, the modified MOF enhanced resin-based composite material was successfully synthesized.
[0074] 1.2 XRD pattern characterization
[0075] The X-ray diffraction (XRD) pattern of the modified MOF enhanced resin-based composite material prepared in Example 1 was measured on a German Bruker D2 X-ray diffractometer. The results are as follows: Figure 2 XRD instrument parameters: the light source is Cu Kα ray, the scanning speed is 10° / min, and the scanning range (2θ) is from 5° to 40°. Figure 2 The XRD spectrum of the composite material shows diffraction peaks at 2θ of 7.15° and 8.25°, which coincide with the peaks of UiO-66-NH2-SH, indicating that UiO-66-NH2-SH@CR11 was successfully synthesized, but the content of MOF in the composite material was small, so the peak intensity was weak.
[0076] 1.3 Specific surface area, pore volume and most probable pore diameter
[0077] The specific surface area, pore volume and pore size of the modified MOF enhanced resin-based composite material prepared in Example 1, CR11 resin and the MOF material prepared in Comparative Example 2 were measured by using the DFT method (macropore) using the ASAP 2640 physical adsorption instrument of Micrometric Company, USA. The results are shown in the following table:
[0078]
[0079] It can be seen that the compounding of MOF materials effectively increases the specific surface area of the resin, thereby exposing more adsorption sites and promoting the enhancement of adsorption performance.
[0080] 1.4 Nitrogen adsorption and desorption experiments
[0081] The results of nitrogen adsorption and desorption experiments are shown in Figure 3 shown.
[0082] The N2 isothermal adsorption and desorption test was performed by using the ASAP 2640 physical adsorption instrument of Micrometric Company of the United States. The results showed that the specific surface area of the modified MOF enhanced resin-based composite material prepared in Example 1 was 434.95 (m 2 / g); pore volume is 0.307 (cm 3 / g); pore size is 33.242nm. Its N2 adsorption-desorption curve is a typical type III adsorption isotherm, indicating that the material is a macroporous material.
[0083] 2. Evaluation of the removal effect of copper ions and antimony ions in sewage
[0084] 2.1. The adsorption capacity of the modified MOF-enhanced resin-based composite material provided in Example 1 for heavy metal ions.
[0085] The test method is as follows:
[0086] (1) Prepare a heavy metal mixed solution.
[0087] The model contaminated liquid is prepared by using GSB 04-1767-2004 standard substance as a metal ion source and diluting with a sodium chloride aqueous solution with a mass fraction of 5%. The model contaminated liquid contains 2 mg / L of each of Al, As, B, Ba, Be, Bi, Cd, Co, Cr, Cu, Fe, Ga, Li, Mg, Mn, Ni, Pb, Sb, Sn, Sr, Ti, Tl, V, and Zn. Take 20 mL of the model contaminated liquid and place it in a 50 mL centrifuge tube, add 20 mg of the modified MOF enhanced resin-based composite material prepared in Example 1, 20 mg of CR11 resin or 20 mg of the MOF material prepared in Comparative Example 2, and then seal the centrifuge tube and place it on a shaker at 200 rpm. After shaking for 60 minutes, take 5 mL of the supernatant, filter it through a 0.1 μm filter membrane, accurately sample it, and use 1% dilute nitric acid for digestion. The concentrations of copper and antimony elements in the digested liquid are detected. Calculate the adsorption amount q e .
[0088] q e =(C0-C t )×20mL÷20mg
[0089] Where, C0 is the initial concentration of heavy metals in the solution, mg / L; C t is the heavy metal concentration in the solution at time t, mg / L.
[0090] The experimental results are as follows Figure 4As shown. Compared with CR11 resin and MOF materials, the composite material has greatly improved adsorption performance for copper ions; for antimony ions, although the adsorption effect of the composite material is not as good as UiO-66-NH2-SH, compared with CR11 resin, the adsorption amount increased from 0.08 mg / L to 0.64 mg / L, an increase of 8 times. It can be seen that the resin matrix and the in-situ grown modified MOF material in the composite material UiO-66-NH2-SH@CR11 can play a synergistic role in the process of removing heavy metal ions such as copper and antimony.
[0091] 2.2. The copper ion and antimony ion removal performance of the modified MOF-enhanced resin-based composite materials prepared in each embodiment and comparative example was evaluated.
[0092] The results are shown in the following table:
[0093]
[0094]
[0095] It can be seen from the test results of each embodiment that the resin MOF composite material provided by the present invention has the ability to remove copper ions and antimony ions in mixed sewage more quickly in a mixed test solution of 24 metals, which proves that the resin MOF composite material provided by the present invention has a stronger anti-interference ability for the adsorption of copper ions and antimony ions.
[0096] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified MOF-enhanced resin-based composite material, characterized in that: The following steps are involved: S1, mixing MOF raw materials, modifiers, resins and solvents, and stirring to obtain a mixture; S2, subjecting the mixture obtained in step S1 to a solvothermal reaction to obtain a modified MOF-enhanced resin-based composite material; Wherein, in step S1, the MOF raw material is composed of ZrCl4 and 2-aminoterephthalic acid, and the modifier is a carboxylic acid containing sulfur element; In step S2, the temperature of the solvent thermal reaction is 100-150°C.
2. The preparation method according to claim 1, characterized in that: In step S1, the modifier is selected from at least one of thioglycolic acid, lipoic acid, and L-cysteine; the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N,N-diethylformamide; and the resin is at least one of CR11 resin, D201 resin, and D113 resin.
3. The preparation method according to claim 2, characterized in that: In step S1, the modifier is thioglycolic acid, the solvent is N,N-dimethylformamide, and the resin is CR11 resin.
4. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of ZrCl4 to 2-aminoterephthalic acid is 0.95-1.05:
1.
5. The preparation method according to claim 4, characterized in that: In step S1, the molar ratio of ZrCl4 to 2-aminoterephthalic acid is 1:
1.
6. The preparation method according to claim 1, characterized in that: In step S1, the ratio of the mass of the MOF raw material, the mass of the modifier, the mass of the resin and the volume of the solvent is 0.5:0.1-7:0.5-5:10-30, in units of g:g:g:mL.
7. The preparation method according to claim 4, characterized in that: In step S1, the ratio of the mass of the MOF raw material, the mass of the modifier, the mass of the resin and the volume of the solvent is 0.5:2:2.5:15, in units of g:g:g:mL.
8. The preparation method according to claim 1, characterized in that: In step S1, the stirring time is 6-12 hours; in step S2, the solvent thermal reaction time is 18-36 hours.
9. A modified MOF-enhanced resin-based composite material obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the modified MOF-enhanced resin-based composite material prepared by the preparation method according to any one of claims 1 to 8 in pollutant treatment.
Citation Information
Patent Citations
Preparation for thiol-functionalization MOFs material and application thereof in adsorption and removal of heavy metal ions in water
CN105175295A
Sulfur-based modified MOF (Metal Organic Framework) membrane for high-efficiency removal of heavy metal ions in blood and preparation method thereof
CN106902649A
Sulfydryl modified MOF (Metal Organic Framework) material, synthesis method and application
CN118745255A
Cited By
Membrane separation technology-based resourceful treatment method for waste containing gold, tantalum, niobium and tin
CN120350222A
A method for processing gold-containing tantalum-niobium-tin waste materials based on membrane separation technology
CN120350222B
